The Relationship between Work-Family Conflict, Emotional Exhaustion, and Work Engagement of Chinese Employees - Duan, Xu (2020)
The aim of this dissertation is to investigate the relationship between work-family conflict, emotional exhaustion, and work engagement of Chinese employees. In this study, quantitative analysis and questionnaire survey method were used. 122 participants participated in this questionnaire survey, and 117 valid questionnaires were obtained. The findings of this study show that, for Chinese employees, work-family conflict is significantly positively correlated with emotional exhaustion, work-family conflict is significantly negatively correlated with work engagement, and emotional exhaustion is significantly negatively correlated with work engagement. In conclusion, employees with more work-family conflict usually have higher levels of emotional exhaustion and lower work engagement. Differences in gender, age, marital status, educational background, and number of children do not lead to significant differences in the level of work-family conflict, emotional exhaustion, and work engagement. This dissertation proposes some long-term and short-term recommendations for companies and employees. The limitation of this dissertation is that it ignores the personal characteristics of employees and the geographical distribution of participants is not absolutely uniform. In future studies, researchers can study the effects of different cities, industries, work systems, and personality traits on the relationship between work-family conflict, emotional exhaustion, and work engagement.